Association of Heart Rate Variability with the Psychosocial Stress Level in Men 41-44 Years Old Living in Moscow - O. M. Drapkina; V. B. Rozanov; A. V. Kontsevaya; O. Yu. Isaykina; G. A. Muromtseva; M. B. Kotova; E. S. Akarachkova (Рациональная фармакотерапия в кардиологии)
Aim. Research of the association of heart rate variability (HRV) with the level of psychosocial stress (PS) and other indicators of the risk of cardiovascular diseases in a sample of 41-44-year-old men living in Moscow.Material and methods. A total of 299 men aged 41-44 years were examined. The study included a clinical examination and a survey using a standard questionnaire. The categorization of risk factors (RF) for cardiovascular diseases (CVD) was carried out in accordance with generally accepted criteria The psychosocial stress was assessed using the Reeder scale. Depending on the psychosocial stress level, all surveyed men were divided into 3 groups by terciles: group 1 (3,28-4,0 points) – mild stress, group 2 (2,71-3,14) – moderate stress, group 3 (1,28-2,57) – severe stress. The analysis of HRV was performed on the basis of a short recording of an electrocardiogram using the original software package.Results. Nonparametric ANOVA showed that the mean [M (95% CI)] values of the HRV time domain (SDNN, rMSSD and the state of regulatory reserves) were lower in the group of men with high PS compared with the group with low PS [25.3 ms (20.9-29.7) versus 40.5 ms (30.7-50.3), p=0.007; 29.5 ms (24.6-34.3) versus 49.5 ms (36.7-62.3), p=0.030; and 46.7 (44.7-48.6) versus 49.7 (48.1-51.4), p=0.019; respectively]. On the contrary, the mean values [M (95% CI)] of the integral indicators of HRV (SI and IVR) were higher in the group of men with high PS [635.8 c.u. (556.2-715.4) versus 488.9 (423.8-554.1), p=0.005; 1172.6 (1045.1-1300.1) versus 904.7 (790.0-1019.4), p=0.003; respectively]. The results of correlation and multiple regression analysis confirmed that these HRV indicators are statistically significantly associated not only with PS, but also with other indicators (age, waist / hip ratio, diastolic blood pressure). However, their predictive value turned out to be low, and the proportion of the explained variance of HRV indices ranged from 2.5 to 13.1%.Conclusion. The weakening of the autonomous regulation of the heart rate with a decrease in the activity of the parasympathetic link, the activation of the central circuit of regulation with the prevalence of sympathetic influences, a decrease in the functional reserves of the heart rate regulation system are associated with an increase in the level of PS and other indicators of the risk of cardiovascular diseases.